Pengaruh Metode Gallery Walk Terhadap Hasil Belajar Seni Rupa Siswa Kelas IV Sekolah Dasar - Sri Mulyani, Dwi; Anggraini, Dwi; Susanti, Atika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Gallery Walk method on Fine Arts knowledge learning outcomes among fourth-grade students at Elementary Schools in Gugus XIV, Bengkulu City. This research is quantitative in nature. The researchmethod used is Quasi-Experimental Design with The Matching Only PretestPosttest Control Group Design as the research design. The population of this study was fourth-grade students of State Elementary Schools in Gugus XIV, Bengkulu City, that have been accredited A. The research sample comprised students from Class IV A and Class IV B at Public Elementary School 42, Bengkulu City, selected using the Cluster Random Sampling technique. The research instrument used was a knowledge-based learning achievement test in the form of multiple-choice questions administered as a pretest and posttest. Data analysis in this studyemployed quantitative analysis using descriptive statistics, prerequisite tests, and hypothesis testing through the t-test. Based on the research findings, a Sig. (2- tailed) value of 0,002 < 0,05 was obtained at a significance level of 5%. The mean score of the experimental class (63,63) was higher than that of the control class (47,90), indicating a significant difference in learning outcomes between the experimental class and the control class. Therefore, it can be concluded that the Gallery Walk method has a significant effect on Fine Arts knowledge learning outcomes among fourth-grade students at Elementary Schools in Gugus XIV, Bengkulu City.